(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To assess the current situation of pressure ulcers and learn about some factors related to pressure ulcers at the Surgical Intensive Care Unit of Bach Mai Hospital. Subject and methods: Cohort study design, selecting the entire sample, using the Braden scale to assess the risk of pressure ulcers in patients at the Surgical Intensive Care Unit, Anesthesia and Resuscitation Center, Bach Mai Hospital. Results: Of the 170 patients participating in the study, the proportion of patients with pressure ulcers accounted for 27.6%. The most common ulcer location was the heel, accounting for 16.5%. Regarding the level of ulcers: level I accounted for 30.4%, level II accounted for 69.6%, no level III and level IV ulcers appeared. There was a statistically significant difference in pressure ulcers and physical condition with p < 0.05; pressure ulcers and ventilator status with p < 0.001. The rate of pressure ulcers in the group of patients with average physical condition is higher than that of patients with thin and overweight physical condition. The rate of patients with mechanical ventilation ulcers > 7 days is higher than that of patients with mechanical ventilation ≤ 7 days. Conclusion: Pressure ulcers are an issue that deserves attention in intensive care units. Early implementation of preventive measures and timely treatment of pressure ulcers is very necessary, especially in patients with mechanical ventilation and immobility. It is necessary to comprehensively assess the risk of pressure ulcers to have an objective assessment, contributing to limiting the appearance and progression of this condition.